O31 Inequalities in reproductive health outcomes during COVID-19 in Britain: national survey (Natsal COVID). (16th June 2022) - Baxter, Andrew; Geary, Rebecca; Dema, Miss Emily; Pérez, Raquel Bosó; Riddell, Julie; Willis, Malachi; Conolly, Anne; Oakley, Laura; Copas, Andrew; Gibbs, Jo; Bonnell, Chris; Sonnenberg, Pam; et al.
Abstract : Introduction: The COVID-19 pandemic presented challenges to delivery of reproductive health services. To explore effects, we examined patterns of contraceptive use, service access and pregnancy planning in the year following the first UK lockdown. Methods: The Natsal-COVID Wave 2 survey was conducted in March-April 2021, one year after the first lockdown began in Britain. We analysed a subset of sexually-active participants aged 18-44 years and described as female at birth. We estimated differences in outcomes by age and markers of vulnerability. We examined changing contraception use, access to and unmet need for contraceptive services, and London Measure of Unplanned Pregnancy scores (LMUP; range 0-12). Results: Of 1, 488 eligible participants, 78.0% were considered at risk of unplanned pregnancies. Of 441 at-risk participants who tried to access contraceptive services, 16.4% faced barriers. Young participants (18-24 years) were most likely to report trying to access contraceptive services (38.4%; (32.2, 45.0); vs 28.4% overall) and to face barriers doing so (OR: 2.87 (1.36, 6.06)). Encountering barriers was more likely among participants reporting no educational qualifications and those reporting symptoms of anxiety or depression. 199 participants reported a pregnancy in the last year. Pregnancies to young participants were less likely to be 'planned' (difference in mean LMUP score: -2.95; (-3.91, -1.99)). Less 'planned' pregnancies were associated with lower social grades and becoming unemployed. Discussion: Young and vulnerable participants were more likely to report difficulties accessing reproductive services and less planned pregnancies during the pandemic. In navigating pandemic recovery, sexual health services should consider the needs of these at-risk groups.